2003
DOI: 10.1172/jci200317856
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stem cells contribute to repair of the ischemically injured renal tubule

Abstract: The paradigm for recovery of the renal tubule from acute tubular necrosis is that surviving cells from the areas bordering the injury must migrate into the regions of tubular denudation and proliferate to re-establish the normal tubular epithelium. However, therapies aimed at stimulating these events have failed to alter the course of acute renal failure in human trials. In the present study, we demonstrate that Lin -Sca-1 + cells from the adult mouse bone marrow are mobilized into the circulation by transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 24 publications
5
143
2
5
Order By: Relevance
“…Several publications showed engraftment and differentiation of grafted SC into renal structures associated with improvement in renal function [3,5,6,7,8,9]. However, other studies demonstrated beneficial effect in spite of low presence or even absence of SC engraftment [10,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several publications showed engraftment and differentiation of grafted SC into renal structures associated with improvement in renal function [3,5,6,7,8,9]. However, other studies demonstrated beneficial effect in spite of low presence or even absence of SC engraftment [10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies [7,8,9,10,12,13,14] have used valuable rodent models to investigate SC therapy in the kidney. However, in small animal models, autologous graft is difficult owing to the size of the animal and immunosuppressive treatments are necessary in order to avoid rejection and enable SC survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the beneficial effects of insulin-derived growth factor observed in experimental animals were not duplicated in a randomized study of patients with clinical ARF (88). A recent exciting approach in this area has been the administration of stem cells or endothelial cells to enhance recovery from acute ischemic renal injury in experimental animals (89)(90)(91)(92). There is ongoing research into the mechanisms whereby injured tubules are relined with new cells actively engaged in DNA synthesis.…”
Section: Figurementioning
confidence: 99%
“…There is evidence that bone marrow-derived cells can migrate to the kidney and form tubular epithelial cells following AKI [4,5,6,7,8]. However, the in vivo contribution of extrarenal cells to kidney regeneration is minimal [9,10,11].…”
Section: Kidney Regeneration Following Akimentioning
confidence: 99%